Pertanggungjawaban Ayah Tiri dalam Melakukan Perbuatan Tindak Pidana terhadap Anak Tiri Asuhannya - Bimantoro, Putra; Israd , Agri Chairunnisa (FOCUS, 2023)
Because child molestation is a serious societal issue, the community must work to stop it, find those responsible, and provide victims with the best possible care. The goals of this research are to (1) ascertain whether the Bandung District Court Panel of Judges' Decision No. 862/Pid.Sus /2020/PN. Bdg. is in accordance with the laws and regulations, and (2) to examine the criminal responsibility of the perpetrators of criminal acts based on Law No. 35 of 2014 against perpetrators of criminal acts of sexual immorality against children. This research used a qualitative legal methodology, namely a methodical normative-jurisdictional of relevant sources. Analysis is used as a method of data collection. Researchers collect facts, details with a constitutional and conceptual approach. The study's primary finding is that (1) Indonesian Criminal Law's provisions for protecting children from sexual crimes are essentially provisions for protecting children from sexual crimes. 862/Pid.Sus/2020/PN.Bdg is the panel judge number for the Bandung District Court's decision. is in accordance with the laws and regulations. The considerations of the Panel of Judges as above are also in line with existing laws and regulations in Indonesia and are based on evidence at trial.